2010
DOI: 10.1128/iai.00925-09
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharide Capsule and Sialic Acid-Mediated Regulation Promote Biofilm-Like Intracellular Bacterial Communities during Cystitis

Abstract: Uropathogenic Escherichia coli (UPEC) is the leading cause of urinary tract infections (UTIs). A murine UTI model has revealed an infection cascade whereby UPEC undergoes cycles of invasion of the bladder epithelium, intracellular proliferation in polysaccharide-containing biofilm-like masses called intracellular bacterial communities (IBC), and then dispersal into the bladder lumen to initiate further rounds of epithelial colonization and invasion. We predicted that the UPEC K1 polysaccharide capsule is a key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
115
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 115 publications
(120 citation statements)
references
References 74 publications
4
115
1
Order By: Relevance
“…In addition to type 1 pili, sialic acid capsule has been implicated in IBC formation and UPEC virulence (3). Recent studies have identified the QseC sensor kinase as another IBC effector, as qseC deletion indirectly impacts expression of type 1 pili and interferes with biofilm formation (25,37).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to type 1 pili, sialic acid capsule has been implicated in IBC formation and UPEC virulence (3). Recent studies have identified the QseC sensor kinase as another IBC effector, as qseC deletion indirectly impacts expression of type 1 pili and interferes with biofilm formation (25,37).…”
mentioning
confidence: 99%
“…Eighty-five percent of community-acquired urinary tract infections (UTI) and 50% of device-associated UTI are caused by uropathogenic Escherichia coli (UPEC) (24), which employ a complex pathogenic cascade in the urinary tract, occupying extracellular and intracellular niches during the course of infection (60). UTI studies in mouse models have identified numerous virulence factors, including adhesins, toxins, iron acquisition systems, capsular structures, flagella, pathogenicity islands, and factors important for biofilm formation (3,26,28,(69)(70)(71). UPEC strains have genes that encode a multitude of chaperone/usher pathway (CUP) pili (14,16,35,45,64).…”
mentioning
confidence: 99%
“…Once in the bladder, E. coli utilizes type 1 pili to invade bladder epithelial cells (11). E. coli bacteria then form a biofilm-like structure known as an intracellular bacterial community (IBC), and cells are coated by the ECM component K1 for protection from host cell recognition (12). The ability of E. coli to recognize multiple environments is critical for production of various UTI-related appendages at the various stages of UTI and IBC formation.…”
mentioning
confidence: 99%
“…Uropathogenic Escherichia coli (UPEC) strains are the primary etiological agent of UTIs and cause 70 to 90% of all such infections (2). UPEC can survive in the urinary tract and cause disease due to a diverse range of virulence factors, including fimbriae (3-6), autotransporter (AT) proteins (7)(8)(9)(10), surface polysaccharides, such as the O antigen and capsule (11)(12)(13), iron acquisition systems (14)(15)(16), and toxins (17)(18)(19)(20)(21).…”
mentioning
confidence: 99%